CSI-based underground personnel behavior identification method - Lei ZHANG; Yue ZHANG; Mingxue LI; Xinguo SHI; Bo ZHAI; Weilong WANG (物联网学报)
To solve the problem of personnel behavior identification under the condition of dust environment and shielding and to promote the coal mine safety production,a personnel identification method based on the Wi-Fi channel state information (CSI) was proposed.The system used Hampel filter and median filter to process the raw CSI data,and utilized the phase information through a linear correction method.The recognition process was divided into the offline stage and online stage.In the offline stage,different activities data was collected to establish the recognition model.While in the online stage,current actions were recognized according to the recognition model.8 different human activities were set in the experiments and the result indicated that the recognition accuracy of this system could reach 95%.